2017
DOI: 10.1002/jctb.5242
|View full text |Cite
|
Sign up to set email alerts
|

Residence time distribution and Peclet number correlation for continuous oscillatory flow reactors

Abstract: BACKGROUND Oscillatory baffled reactors have good prospect for use in batch to continuous transition for many industries. For reliable design and scale up it is essential to mathematically describe mixing and flow pattern of oscillatory flow. The aim of this study is to investigate the effects of operating conditions on residence time distribution (RTD) of liquid phase in a continuous oscillatory baffled reactor (COBR) and to propose a correlation that accurately describes the flow pattern. RESULTS Analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…RTD experiments have been carried out previously in various setups of the oscillatory baffled flow equipment with internal diameters between 4 and 50 mm. These assessments suggest that operating conditions ensuring near-plug flow operation can be achieved in these systems and that superior heat transfer can be obtained when using oscillatory baffled flow conditions when compared to no oscillation and/or no baffles present. Studies measuring axial dispersion in oscillatory flow systems have utilized a wide range of geometries and operating conditions, and a summary of this literature can be found in the Supporting Information.…”
Section: Introductionmentioning
confidence: 99%
“…RTD experiments have been carried out previously in various setups of the oscillatory baffled flow equipment with internal diameters between 4 and 50 mm. These assessments suggest that operating conditions ensuring near-plug flow operation can be achieved in these systems and that superior heat transfer can be obtained when using oscillatory baffled flow conditions when compared to no oscillation and/or no baffles present. Studies measuring axial dispersion in oscillatory flow systems have utilized a wide range of geometries and operating conditions, and a summary of this literature can be found in the Supporting Information.…”
Section: Introductionmentioning
confidence: 99%
“…Flow rates resulting in Re n < 10 report that Re o has little impact on axial dispersion, with axial dispersion through baffled sectors increasing due to lack of transport along the reactor length . Furthermore, a minimum net oscillatory Reynolds number of 130 must be met to achieve near-plug-flow conditions alongside adequate mixing within a continuous OBR, which could incur very high velocity ratios at these ultralow flow rates. In a study conducted by Slavanić et al using low Re n , they found that when high x 0 and low f are used to reach a higher Re o , the fluid operates with low levels of axial dispersion and with adequate mixing, providing ψ > 1 .…”
Section: Resultsmentioning
confidence: 99%
“…42 Furthermore, a minimum net oscillatory Reynolds number of 130 must be met to achieve near-plug-flow conditions alongside adequate mixing within a continuous OBR, 53 which could incur very high velocity ratios at these ultralow flow rates. In a study conducted by Slavanićet al using low Re n , they found that when high x 0 and low f are used to reach a higher Re o , the fluid operates with low levels of axial dispersion and with adequate mixing, 53 providing ψ > 1. 54 The current research found a trend of higher TiS values at x 0 (8−12 mm) in the single-column experiments compared to values below 6 mm.…”
Section: Change Of Rtd Across the Reactor Lengthmentioning
confidence: 99%
“…where v its velocity of the protoplasm. We have estimated the oscillatory (i.e., maximum) Reynolds number Re max [43] attained during protoplasmic flow in the strands of P. polycephalum using data directly available from our experiments and from literature. The maximum Reynolds number is obtained using the maximum velocity attained during shuttle streaming, which in our experiments was 1.20 mm s −1 (figure 2), [22], respectively.…”
Section: Laminar Flowmentioning
confidence: 99%